Development Prospects of the Art of Dance (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
As we all know, the world of art is priceless with its diversity. In particular, the world of "dance", which is considered a symbol of elegance and beauty, is developing day by day, and the development of the field is reaching high peaks. The charm and uniqueness of the art of dance has given special pleasure to art lovers in all eras. However, the art of dance has gone through a long path of development, oppression and restrictions until it became what it is today. It was polished in different ways in different periods and manifested in different forms. This article also talks about the stages of historical development of the art of "dance", the achievements made over the years and some shortcomings.